Mysticism in The Brothers Karamazov - Stoeber, Michael (Toronto journal of theology, 2015)
The article explores the mystical quality of religious experiences of major characters in Fyodor Dostoevsky's The Brothers Karamazov. It analyzes them as they are presented through the elder Zosima and his brother Markel, as well as Dmitri and Alyosha Karamazov. It also clarifies natural non-religious and diabolical mystical experiences, as they are developed especially through Ivan Karamazov and Pavel Smerdyakov. Although Dostoevsky in his notes and other comments expresses some ambivalence toward mysticism, the article explores the significant role mystical experiences play in his modern revision of Orthodox Christianity.